Assessing housing and basic services access for internally displaced persons in conflict-affected Gaza Strip: a mixed-methods study - Sabah, Faisal Yousef (Frontiers in Public Health, 2025)
BackgroundThe Gaza Strip’s protracted conflict has created a severe humanitarian crisis, leaving internally displaced persons (IDPs) with limited access to adequate housing and basic services. This study addresses a critical gap in understanding the housing and service disparities experienced by IDPs in Gaza, aiming to inform targeted policy interventions.MethodsA mixed-methods approach was employed, integrating quantitative and qualitative data collection. A cross-sectional survey was conducted with 400 IDP households selected through stratified random sampling across the five governorates of Gaza. In addition, 20 in-depth interviews and 4 focus group discussions captured the lived experiences of IDPs. Quantitative data were analyzed using descriptive and inferential statistics, while thematic analysis was applied to qualitative data.ResultsQuantitative findings revealed that 63% of IDP households live in inadequate housing, with North Gaza and Rafah exhibiting the highest rates of inadequacy (75 and 71%, respectively). Furthermore, 38% of households reported reliable access to clean water, and 52% lacked consistent electricity. Qualitative analysis highlighted the psychological toll of displacement, with many IDPs expressing feelings of hopelessness and concerns over the sustainability of temporary shelters.ConclusionThis study underscores the urgent need for comprehensive interventions to improve IDP housing conditions and access to essential services in Gaza. Sustainable housing solutions, enhanced infrastructure, and the inclusion of IDP perspectives in policymaking are vital for alleviating the ongoing humanitarian crisis.